Prohibited Contracts and Sharia Economic Law Review of Counterfeit Goods Practices on E-Commerce Platforms - Helmi Fitriansyah; Siti Aisyah (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2024)
The proliferation of counterfeit goods on e-commerce platforms presents a significant challenge to the enforcement of Sharia economic law in the digital age. Such practices infringe upon intellectual property rights and contravene core Islamic principles of justice (‘adl) and honesty (sidq). This study critically examines violations of Sharia principles inherent in the sale of counterfeit goods, with a focus on prohibited contractual practices such as tadlis (fraudulent misrepresentation) and gharar (excessive uncertainty), while proposing actionable solutions to cultivate a Sharia-compliant digital commerce ecosystem. Employing a literature review methodology, this research analyzes secondary data derived from regulatory frameworks, scholarly works, and case studies. Findings reveal that the sale of counterfeit goods breaches fundamental requirements for valid contracts under Sharia law, undermines consumer and producer rights, and erodes societal ethical standards. Key challenges include inadequate regulatory oversight of digital transactions, limited consumer awareness, and the absence of Sharia principles in e-commerce governance frameworks. To address these issues, the study advocates for multistakeholder collaboration among governments, e-commerce platforms, and civil society. Recommendations include the integration of Sharia-compliant regulations into digital trade policies, leveraging artificial intelligence for proactive detection of illicit products, and targeted consumer education campaigns to highlight the ethical and legal ramifications of counterfeit trade. The implications of this research extend to fostering a transparent, equitable, and Sharia-aligned digital marketplace, thereby advancing the sustainability of Islamic commerce in the digital era and reinforcing ethical consumption practices in alignment with Islamic jurisprudence.